2019
DOI: 10.1051/bioconf/20191202006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la composición y calidad del color de vinos tintos Tannat elaborados por maceración pre-fermentativa en caliente

Abstract: Durante la vendimia 2016 se elaboraron vinos tintos Tannat por maceración pre-fermentativa en caliente (una hora de calentamiento a 60–70 ∘C seguido de una maceración fermentativa de 7 días) y maceración tradicional (maceración fermentativa de 7 días) con el objetivo de evaluar su concentración en compuestos fenólicos y color durante la conservación. Las vinificaciones se realizaron por triplicado en recipientes de 10 litros de capacidad. Se determinó la composición básica del vino, color, concentración de fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…UV 280 nm assay. The tannin content was directly determined by measuring the optical density at 280 nm using a 10-mm quartz cuvette ( Piccardo and González-Neves, 2013 ), with a Cary 100 Bio UV–Vis spectrophotometer (Agilent, Ireland). Calibration was performed using aqueous solutions of the original tannin extracts (5–100 ppm) as reference standards.…”
Section: Methodsmentioning
confidence: 99%
“…UV 280 nm assay. The tannin content was directly determined by measuring the optical density at 280 nm using a 10-mm quartz cuvette ( Piccardo and González-Neves, 2013 ), with a Cary 100 Bio UV–Vis spectrophotometer (Agilent, Ireland). Calibration was performed using aqueous solutions of the original tannin extracts (5–100 ppm) as reference standards.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, since tannin extraction is much more dependent on increasing ethanol content to encourage its solubilization, one approach to obtain a higher extraction of polyphenolic compounds consists in fermenting grapes after heating with solid parts of the grapes, as in standard vinification with shorter maceration time. This alternative was found to increase total phenolic index, color intensity and anthocyanins content in wine 58%, 25% and 45%, respectively [29].…”
Section: Impact Of the Treatment In The Composition Of Winementioning
confidence: 97%
“…Piccardo and González-Neves [29] reported that the extraction of anthocyanins after thermovinification was practically immediate. As consequence the anthocyanin concentration and the color intensity in the first days of fermentation were 21% and 45% higher, respectively, than in control.…”
Section: Impact Of the Treatment In The Composition Of Winementioning
confidence: 99%